Mise en place d’un modèle d’intervention psychoéducatif adapté à la réalité haïtienne en passant par la co-construction : un projet pilote implanté au centre d’accueil de Delmas 3 à Port-au-Prince - Mélanie Poitras; Claudine Jacques (Études Caribéennes)
In Haiti, accessibility to specialized services and the lack of psychiatric hospitals exacerbates adaptation problems (Lecompte and Raphael 2010a; Nicolas et al, 2012; WHO-AIMS, 2011). The health professionals at the Centre d’accueil de Delmas 3 respond to the complex needs of young street children. In Quebec, several evidence-based intervention models have shaped our clinical practice for young children with behavior disorders. In fact, rehabilitation interventions are based on the psychoeducational model. The current research project had two goals: 1) Examine whether a collaborative approach would facilitate and ensure that the implementation of an intervention program would be ongoing and long-lasting in Haiti; 2) Explore whether the psychoeducational model could respond to the needs of a Haitian youth center. Qualitative methods were used to bring together partners in the research (Hamel, Cousineau and Vézina, 2010). First, educators followed a two days training developed to respond the specific needs. Second, interventions were implemented by researchers in collaboration with the stakeholders. This pilot project has shown that a collaborative approach encourages training and the level of participants' satisfaction. Futher, this experience showed that the psychoeducational model could very well fit the needs of a Haitian youth center. The psychoeducative model can yield responses adapted to the needs of people accounting for the characteristics of the environment (Renou, 2005).